Microglia Activation and Immunomodulatory Therapies for Retinal Degenerations - Rashid, Khalid; Wolf, Anne; Langmann, Thomas (Frontiers in Cellular Neuroscience, 2018)
A chronic pro-inflammatory environment is a hallmark of retinal degenerative diseases and neurological disorders that affect vision. Inflammatory responses during retinal pathophysiology are orchestrated by microglial cells which constitute the resident immune cell population. Following activation, microglia cells lose their ramified protrusions, proliferate and rapidly migrate to the damaged areas and resolve tissue damage. However, sustained presence of tissue stress primes microglia to become overreactive and results in the excessive production of pro-inflammatory mediators that favor retinal degenerative changes. Consequently, interventions aimed at overriding microglial pro-inflammatory and pro-oxidative properties may attenuate photoreceptor demise and preserve retinal integrity. We highlight the positive effects of ligands for the translocator protein 18 kDa (TSPO) and the cytokine interferon beta (IFN-β) in modulating microgliosis during retinal pathologies and discuss their plausible mechanisms of action.